Telemedicine: problematic (non) regulation aspects and future perspectives - Gulbinas, Alanas; Jogminaitė, Kamilė (Vilnius University Open Series, 2021)
This article analyzes the main problematic aspects of (non) regulation and future perspectives in the field of telemedicine.